Indoor location tracking technology evaluation by using spherial fuzzy TOPSIS method - Oztaysi, Basar; Kahraman, Cengiz; Onar, Sezi Cevik; Otay, Irem (World Scientific Publ Co Pte Ltd, 2020)
With the emerging technologies, collecting and processing data about the behaviors of customers or employees in a specific location has become possible. The purpose of this paper is to evaluate existing data collection technologies. Technology evaluation problem is handled as a multi-criteria decision-making (MCDM) problem. In this manner, a decision model containing four criteria and four alternatives are formed. In this study, we use Spherical Fuzzy TOPSIS method to solve the technology selection problem.
15th Symposium of Intelligent Systems and Knowledge Engineering (ISKE) held jointly with 14th International FLINS Conference (FLINS) -- AUG 18-21, 2020 -- Cologne, GERMANY
Keywords: Technology Selection; Spherical Fuzzy Sets; Topsıs; Model; Paths